ChemInform Abstract: Novel 5‐Acetyl‐3‐aryl‐2‐thioxo‐dihydropyrimidine‐4, 6(1H, 5H)‐diones: One Pot Three‐Component Synthesis, Characterization and Antibacterial Activity. Issue 35 (2nd September 2014) - Saeed, Aamer; Abbas, Naeem; Ashraf, Zaman; Bolte, Michael
Abstract The title compounds (IV) are screened for their preliminary antibacterial activity against a panel of Gram‐positive and Gram‐negative bacteria.